Density fluctuations for a zero-range process on the percolation cluster - Gonçalves, Patrícia (2009)
We prove that the density fluctuations for a zero-range process evolving on the $d$-dimensional supercritical percolation cluster, with $d≥{3}$, are given by a generalized Ornstein-Uhlenbeck process in the space of distributions $\mathcal{ S}'(\mathbb {R}^d)$.